Method for preparing flexible asymmetric supercapacitor through one-pot method and application
The flexible asymmetric supercapacitor was prepared by a one-pot method, and the solution was induced to layer and form an interfaceless structure using magnetic drive, which solved the problem of poor performance of flexible supercapacitors in multiple scenarios, and achieved efficient electrochemical performance and structural stability. Simplified the preparation process.
Patent Information
- Application Number
- CN202411281688.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-10
AI Technical Summary
Existing flexible supercapacitors have poor performance under multi-scenario application conditions, especially due to electron and ion transmission barriers at the positive electrode/electrolyte/negative electrode interface, resulting in relative displacement and performance degradation caused by mechanical stress. The traditional construction method is complex and time-consuming. Exhausted.
A flexible asymmetric supercapacitor is prepared by one-pot method, and the solution is induced to layer by magnetic driving to form an interfaceless sandwich structure. Directly forming in one piece does not require the preparation of positive and negative electrodes and electrolytes separately. The combination of ethylene-vinyl alcohol copolymer and conductive energy storage materials is used. , a lower electrode layer, an electrolyte layer and an upper electrode layer are formed.
The high area specific capacity and structural stability of flexible supercapacitors are realized, the electrochemical performance and bending and twist resistance are improved, the preparation process is simplified, and the interface transfer resistance is reduced.
Smart Images

Figure HDA0005041825150000011 
Figure HDA0005041825150000012 
Figure HDA0005041825150000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to energy storage, and in particular to a method for preparing a flexible asymmetric supercapacitor by a one-pot process and application thereof. Background Art
[0002] With the explosive growth of flexible wearable electronic devices such as wearable sensors, flexible displays, and artificial skin, flexible energy storage devices have entered a period of vigorous development as a key power source. In order to meet the wider application environment requirements of flexible wearable electronic devices, flexible energy storage devices should be designed to work not only under ordinary conditions (bending, twisting, and folding), but also under extreme conditions (impact, puncture, rolling, and washing). Multi-scenario application conditions have brought new challenges to the field of flexible energy storage. Among the many energy storage systems, supercapacitors have the advantages of high power density, long cycle life, and high safety, and are expected to develop into flexible supercapacitors for multi-scenario applications. In general, the actual performance of flexible supercapacitors depends mainly on the flexible electrodes (positive and negative electrodes), electrolytes, and device configurations. Despite significant progress in the design and development of flexible anodes, cathodes, and quasi-solid gel polymer electrolytes or solid electrolytes with excellent electrochemical and mechanical properties, the performance provided by the assembled flexible supercapacitors is far from expected, let alone multi-scenario applications. The performance gap is caused by the sandwich device configuration of simple stacked components with flexible positive electrodes, electrolytes, and negative electrodes (positive electrode|electrolyte|negative electrode). The derived cathode / electrolyte and electrolyte / anode interfaces hinder the electron and ion transport between them, and more seriously, become the weakest part of the device due to weak physical interactions. High mechanical stress leads to the first disintegration at the interface, and then to the relative displacement between cathode|electrolyte|anode, resulting in configuration collapse and rapid performance degradation of the device under multi-scenario application conditions.
[0003] Integrated flexible supercapacitors have become the focus of future development of science and society. However, there are many solutions to the problem of what method to use to construct an integrated flexible supercapacitor, such as in-situ polymerization, traditional layer-by-layer stacking, and layer-by-layer filtration. But at the same time, the traditional method of constructing an integrated supercapacitor is too complicated. For example, when constructing an integrated supercapacitor by in-situ polymerization, the electrode materials of the positive and negative electrodes need to be slowly grown on the polymer of the intermediate electrolyte layer by in-situ polymerization. For example, when constructing an integrated supercapacitor by the traditional layer-by-layer stacking method, each layer of electrode and electrolyte needs to be prepared separately and then stacked. These methods are not only time-consuming and labor-intensive, but also costly, and often have little effect on the road to the integration of flexible supercapacitors.
[0004] Whether it is the traditional layer-by-layer stacking method, in-situ polymerization method or layer-by-layer filtration method in the process of preparing integrated supercapacitors, many steps are often required for preparation. For example, in the traditional layer-by-layer stacking method, different positive and negative electrode films must be prepared, and the electrolyte must be prepared separately, and then the three layers are stacked layer by layer and bonded by cross-linking or other methods. Not only is it time-consuming, the material preparation cycle is long, and it cannot be prepared in large quantities in a unified manner. For example, in the in-situ polymerization method, the positive electrode and / or negative electrode must be cultivated on the electrolyte. After the positive and negative electrode cultivation is completed, it is necessary to cut them around. These all take a lot of time and steps to prepare supercapacitors.
[0005] Therefore, it is necessary to provide a method for preparing a supercapacitor by directly forming the supercapacitor in one piece without separately preparing or assembling the positive and negative electrodes and the electrolyte to solve the above problems. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a one-pot method for preparing a flexible asymmetric supercapacitor, which does not require the separate preparation or assembly of positive and negative electrodes and electrolytes, and directly forms an interface-free flexible asymmetric supercapacitor in one piece, and the supercapacitor has good mechanical properties and electrochemical properties.
[0007] The present invention also provides the supercapacitor.
[0008] The present invention also provides application of the supercapacitor.
[0009] A first aspect of the present invention provides a method for preparing a supercapacitor, the method comprising the following steps:
[0010] S1, heating and stirring ethylene-vinyl alcohol and an organic solvent to obtain an ethylene-vinyl alcohol copolymer solution;
[0011] S2, stirring and mixing the first conductive material, the first energy storage material and the solvent to obtain the first conductive energy storage material, stirring and mixing the second conductive material, the second energy storage material and the solvent to obtain the second conductive energy storage material;
[0012] S3, mixing the first conductive energy storage composite material, the second conductive energy storage composite material and the ethylene-vinyl alcohol copolymer solution, and using an externally applied magnetic field to separate the mixture into layers to obtain a first electrode layer, an electrolyte layer and a second electrode layer;
[0013] S4. Placing the multilayer mixture in an electrolyte to obtain a supercapacitor.
[0014] The preparation method according to the first aspect of the present invention has at least the following beneficial effects:
[0015] The preparation method of the present invention induces the stratification of the solution through magnetic drive to form a non-interface sandwich structure supercapacitor, and the first conductive energy storage composite material and the second conductive energy storage composite material corresponding to the lower electrode layer and the upper electrode layer are respectively formed on both sides of the polymer by magnetic drive and gravity sedimentation in the ethylene-vinyl alcohol copolymer to form the lower electrode layer, the upper electrode layer and the intermediate electrolyte layer. In the process of preparing or synthesizing the conductive energy storage material, the present invention should dope conductive materials with different contents so that the conductive material covers the energy storage material, and then obtain the conductive energy storage composite material; the lower electrode layer is prepared by a hydrothermal method using a non-magnetic energy storage material, and sinks in the ethylene-vinyl alcohol copolymer by gravity and forms a stratification; the upper electrode layer is prepared by an induced synthesis method using a magnetic energy storage material, and floats in the ethylene-vinyl alcohol copolymer by a magnetic drive method.
[0016] The preparation method of the present invention mixes the first conductive energy storage material, the second conductive energy storage material and the ethylene-vinyl alcohol copolymer in one pot, and directly forms the flexible asymmetric supercapacitor in one pot through magnetic drive without separately preparing the positive electrode, the negative electrode and the electrolyte. This method can not only effectively fuse the interface between the electrode|electrolyte|electrode of the supercapacitor and reduce the interface transfer resistance, thereby improving the area specific capacity of the flexible supercapacitor, but also the interface-free supercapacitor can also have structural stability under different use environments at the same time, and can improve the electrochemical performance, bending resistance and torsional deformation resistance of the supercapacitor itself.
[0017] The preparation process of the scheme of the present invention is simple to operate and has good industrial application prospects.
[0018] According to some embodiments of the present invention, in step S1, the organic solvent is selected from at least one of aprotic polar solvents, aromatic hydrocarbons, halogenated hydrocarbons, acetates, ether solvents or ketone solvents.
[0019] According to some embodiments of the present invention, the number of carbon atoms in the aromatic hydrocarbon is 6-10.
[0020] According to some embodiments of the present invention, the halogenated hydrocarbon includes at least one of chlorobenzene, bromobenzene, trichlorotoluene, dichloromethane, chloroform, 1,2-dichloroethane or carbon tetrachloride.
[0021] According to some embodiments of the present invention, the acetate is selected from at least one of methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, n-butyl acetate or isobutyl acetate.
[0022] According to some embodiments of the present invention, the ether solvent is selected from at least one of tetrahydrofuran, tetrahydropyran, 2-methyltetrahydrofuran, dioxane, ethylene glycol dimethyl ether or ethylene glycol diethyl ether.
[0023] According to some embodiments of the present invention, the ketone solvent is selected from at least one of acetone, butanone, cyclohexanone, methyl ethyl ketone or methyl isopropyl ketone.
[0024] According to some embodiments of the present invention, the aprotic polar solvent includes at least one of an aprotic, non-polar solvent and an aprotic, polar solvent.
[0025] According to some embodiments of the invention, the aprotic, non-polar solvent comprises at least one of benzene, diethyl ether and carbon tetrachloride.
[0026] According to some embodiments of the invention, the aprotic, non-polar solvent comprises at least one of benzene, diethyl ether and carbon tetrachloride.
[0027] According to some embodiments of the present invention, the aprotic, polar solvent comprises at least one of dimethyl sulfoxide, N,N-dimethylformamide, and acetone.
[0028] According to some embodiments of the present invention, the content of vinyl alcohol in the ethylene-vinyl alcohol copolymer is 10% to 73%, for example, 10%, 30%, 48%, 52%, 65%, or 73%.
[0029] According to some embodiments of the present invention, in step S2, the first conductive material and the second conductive material are selected from at least one of carbon nanotubes, graphene, porous carbon, carbon black or carbon fiber.
[0030] According to some embodiments of the present invention, in step S2, the first energy storage material includes at least one of polyaniline, polypyrrole, polythiophene, manganese dioxide, copper oxide, magnesium oxide, vanadium oxide, aluminum oxide, calcium oxide, cuprous oxide, zinc oxide, sodium oxide, potassium oxide and titanium oxide.
[0031] Preferably, in step S2, the first energy storage material includes at least one of polyaniline, polypyrrole, polythiophene and manganese dioxide.
[0032] More preferably, in step S2, the first energy storage material is manganese dioxide.
[0033] According to some embodiments of the present invention, in step S2, the second energy storage material includes at least one of iron oxide, nickel oxide, cobalt oxide, ruthenium oxide, hydroxylated iron oxide and ferrosoferric oxide.
[0034] Preferably, in step S2, the second energy storage material includes at least one of iron oxide, nickel oxide, cobalt oxide, ruthenium oxide and hydroxylated iron oxide.
[0035] More preferably, in step S2, the second energy storage material is hydroxylated iron oxide.
[0036] The hydroxylated iron oxide described in the present invention is spherical superparamagnetic β-FeOOH nanoparticles.
[0037] According to some embodiments of the present invention, in step S2, the mass ratio of the first conductive material to the first energy storage material is 1 to 10:1.
[0038] Preferably, in step S2, the mass ratio of the first conductive material to the first energy storage material is 2.3-9:1.
[0039] According to some embodiments of the present invention, in step S2, the mass ratio of the second conductive material to the second energy storage material is 1 to 10:1.
[0040] Preferably, in step S2, the mass ratio of the second conductive material to the second energy storage material is 2.3-9:1.
[0041] According to some embodiments of the present invention, the content of carbon nanotubes in the first conductive energy storage material is 60-70%.
[0042] According to some embodiments of the present invention, the content of carbon nanotubes in the second conductive energy storage material is 60-70%.
[0043] According to some embodiments of the present invention, in step S3, the mass ratio of the first conductive energy storage composite material, the second conductive energy storage composite material and the ethylene-vinyl alcohol copolymer solution is (1-3): (1-3):1000.
[0044] Preferably, in step S3, the mass ratio of the first conductive energy storage composite material, the second conductive energy storage composite material and the ethylene-vinyl alcohol copolymer solution is 3:3:1000.
[0045] According to some embodiments of the present invention, the concentration of the ethylene-vinyl alcohol copolymer solution is 0.4-0.6 g / mol.
[0046] According to some embodiments of the present invention, in step S3, the intensity of the magnetic field is 20-25 emu / g.
[0047] Preferably, in step S3, the intensity of the magnetic field is 23-24emu / g.
[0048] More preferably, in step S3, the intensity of the magnetic field is 23.6emu / g.
[0049] According to some embodiments of the present invention, in step S3, a magnet is disposed above the mixture, and the distance between the magnet and the mixture is 0.1 to 100 cm.
[0050] According to some embodiments of the present invention, in step S4, the electrolyte includes at least one of an aqueous solution of lithium nitrate, lithium chloride, sulfuric acid or potassium hydroxide.
[0051] According to some embodiments of the present invention, in step S4, the concentration of the solute in the electrolyte is 0.1-4M.
[0052] According to some embodiments of the present invention, the stirring speed in each step is 300-1000 rpm.
[0053] According to some embodiments of the present invention, the stirring time in each step is 30 to 300 minutes.
[0054] According to some embodiments of the present invention, in step S1, the reaction temperature is 100-120°C.
[0055] According to some embodiments of the present invention, in step S2, the reaction temperature is 70-90°C.
[0056] According to some embodiments of the present invention, in step S2, the reaction temperature is 100-400°C.
[0057] According to another aspect of the present invention, a flexible asymmetric supercapacitor prepared by the above preparation method is provided, wherein the supercapacitor comprises an electrolyte layer and an upper electrode layer and a lower electrode layer respectively arranged on both sides of the electrolyte;
[0058] The raw material for preparing the electrolyte layer is ethylene-vinyl alcohol copolymer;
[0059] The raw materials for preparing the lower electrode layer include a first conductive material and a first energy storage material, wherein the first energy storage material is a non-magnetic material;
[0060] The raw materials for preparing the upper electrode layer include a second conductive material and a second energy storage material, wherein the second energy storage material is a magnetic material.
[0061] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:
[0062] The highly deformable flexible asymmetric supercapacitor of the present invention provides the supercapacitor with more excellent mechanical and electrochemical properties, with a capacitance retention rate of 99% and 96% after 5000 bending and twisting cycles, and maintains more than 93% of the initial capacitance under extreme conditions, including cutting, rolling, hammering, puncturing, sewing, immersion and washing in water.
[0063] According to another aspect of the present invention, a flexible electronic device or a wearable electronic device is provided, comprising a flexible asymmetric supercapacitor obtained by the preparation method.
[0064] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0066] Figure 1 The area specific capacitance diagram of the supercapacitor in the present invention includes Comparative Example 1, Comparative Example 2 and Comparative Example 3 in Figure a, and Comparative Example 4, Comparative Example 5 and Example 1 in Figure b.
[0067] Figure 2 The scanning electron microscope images of the supercapacitors of the present invention including Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1, wherein a is Comparative Example 1, b is Comparative Example 2, c is Comparative Example 3, d is Comparative Example 4, e is Comparative Example 5, and f is Example 1;
[0068] Figure 3 The scanning electron microscope images of the supercapacitors prepared in Comparative Examples 6 and 7 and Example 1 of the present invention;
[0069] Figure 4 The impedance and area specific capacitance diagrams of the supercapacitors prepared in Comparative Examples 6 and 7 and Example 1 of the present invention;
[0070] Figure 5 The ultra-depth three-dimensional microscope images of the supercapacitors prepared in Comparative Examples 6 and 7 and Example 1 of the present invention; wherein a is Comparative Example 6, b is Comparative Example 7, and c is Comparative Example 1;
[0071] Figure 6 Comparison graph a of elastic modulus, tensile strength and elongation at break and graph b of peel strength of supercapacitors prepared in comparative examples 6 and 7 of the present invention and embodiment 1;
[0072] Figure 7 The stress-strain curves of the supercapacitors prepared in Comparative Examples 6 and 7 and Example 1 of the present invention;
[0073] Figure 8 The scanning electron microscope images of the supercapacitors prepared in Comparative Example 8 and Examples 1 and 2 of the present invention;
[0074] Fig. 9 Impedance and area specific capacitance diagrams of supercapacitors prepared in Comparative Example 8 and Examples 1 and 2 of the present invention;
[0075] Fig.10Comparison of elastic modulus, tensile strength and elongation at break of supercapacitors prepared in Comparative Example 8 and Examples 1 and 2 of the present invention (Figure a) and peel strength (Figure b);
[0076] Fig.11 The stress-strain curves of the supercapacitors prepared in Comparative Example 8 and Examples 1 and 2 of the present invention;
[0077] Fig.12 The specific capacitance change, cyclic voltammetry curve and electrochemical impedance spectrum of the supercapacitor prepared in Example 1 of the present invention when bent from 0° to 90° and 180°;
[0078] Fig.13 The capacitance change and the corresponding cyclic voltammetry curve of the supercapacitor prepared in Example 1 of the present invention after being bent repeatedly between 0° and 180° for 5000 times;
[0079] Fig.14 The specific capacitance change, cyclic voltammetry curve and electrochemical impedance spectrum of the supercapacitor prepared in Example 1 of the present invention when twisted from 0° to 20°, 40° and 60°
[0080] Fig.15 The capacitance change and the corresponding cyclic voltammetry curve of the supercapacitor prepared in Example 1 of the present invention when repeatedly twisted between 0° and 60° for 5000 times;
[0081] Fig.16 The ultra-depth three-dimensional microscope images of the supercapacitors prepared in Example 1 and Comparative Example 9 are shown; a is for Example 1 and b is for Comparative Example 9;
[0082] Fig.17 The cycle stability of the supercapacitors prepared in Example 1 and Comparative Example 9 of the present invention, the capacitance change of Example 1 after 5000 cycles and the capacitance change of Comparative Example 9 after 5000 cycles and the corresponding cyclic voltammetry curves;
[0083] Fig.18 A comparison diagram of the area specific capacitance of the supercapacitor prepared in Example 1 of the present invention and the supercapacitor prepared in Comparative Example 9;
[0084] Fig.19 A comparison diagram of electrochemical impedance spectra of the supercapacitor prepared in Example 1 of the present invention and the supercapacitor prepared in Comparative Example 9;
[0085] Fig. 20The application display diagram of the supercapacitor prepared in Example 1 of the present invention in various shapes and under various conditions to light up the electronic clock; Figure a is a display diagram of supercapacitors of different shapes lighting up the electronic clock, Figure b is a diagram of the capacity retention rate and area size corresponding to supercapacitors of different shapes, Figure c is a diagram of the capacity retention rate of the supercapacitor under different hammer hit times, and Figure d is a diagram of the capacity retention rate of the supercapacitor under different vehicle runover times;
[0086] Fig.21 It is an application demonstration diagram of the supercapacitor prepared in Example 1 of the present invention in lighting up electronic clocks in various shapes and under various conditions; Figure e is a diagram of the capacity retention rate of the supercapacitor at different immersion times, Figure f is a diagram of the capacity retention rate of the supercapacitor at different flushing times, Figure g is a diagram of the capacity retention rate of the supercapacitor at different numbers of holes in the punching test, and Figure h is a diagram of the capacity retention rate of the supercapacitor under different numbers of pinholes;
[0087] Fig. 22 Three supercapacitors prepared in Example 1 of the present invention are connected in series to power a smart watch and test heart rate graph a, power a pulse oximeter and test blood oxygen and pulse graph b, and power a smart vehicle locator and its positioning cycle route map c. DETAILED DESCRIPTION
[0088] The embodiments of the present invention are described in detail below, and the same or similar reference numerals throughout the embodiments represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0089] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0090] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0091] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0092] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0093] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0094] Example 1
[0095] This embodiment provides a method for preparing a flexible asymmetric supercapacitor, comprising the following steps:
[0096] (1) 20.0 g of ethylene-vinyl alcohol having a vinyl alcohol content of 30% and 50 mL of dimethyl sulfoxide (DMSO) solution were mixed and then mechanically stirred at 120° C. at 500 r / min for 90 min to obtain an ethylene-vinyl alcohol copolymer solution (the concentration of the ethylene-vinyl alcohol copolymer was 0.4 g / mL).
[0097] (2) 2.5 g potassium permanganate KMnO4 (12.5 mol), 5.8 g multi-walled carbon nanotubes (Nanocyl NC7000 series), and 100 mL deionized water were mixed and mechanically stirred at 500 r / min for 30 min at 80°C, and then 0.5 mL of concentrated sulfuric acid was added and mechanically stirred at 500 r / min for 60 min at 80°C, and then transferred to an oil bath at 80°C and mechanically stirred at 500 r / min for 60 min. Finally, the obtained solution was filtered, washed, dried, and ground to form a carbon-coated manganese dioxide positive electrode material MnO 2 @MWNT. 2 @MWNT carbon nanotube content is 70%)
[0098] (3) 1.62 g of ferric chloride hexahydrate FeCl·6H 2O (10 mmol), 0.85 g oleic acid (3 mmol), 3.78 g multi-walled carbon nanotubes, and 50 mL deionized water were mixed, and 3.95 g NH 4 HCO 3 (50mmol) and 0.18g ethyl acetate were mixed in a 100°C oil bath with mechanical stirring at 1000r / min for 10min to make it fully mixed, then the stirring was stopped, and the mixture was placed in a 100°C oil bath for 5min and taken out, finally washed and filtered, and then placed in a 400°C tubular furnace under a nitrogen environment for calcination for 60min. After calcination, the mixture was cooled, taken out and ground into fine powder to obtain a superparamagnetic carbon-coated iron oxide negative electrode material FeOOH@MWNT. (The carbon nanotube content in FeOOH@MWNT is 70%)
[0099] (4) 6 mg of carbon-coated manganese dioxide positive electrode material MnO 2 The mixture of 6 mg superparamagnetic carbon-coated iron oxyhydroxide negative electrode material FeOOH@MWNT and 2.0 g ethylene-vinyl alcohol copolymer solution was poured into a polytetrafluoroethylene mold and mixed at room temperature at 100 r / min for 5 min. Then, a super-strong magnetic magnet was placed above the solution to adsorb the FeOOH@MWNT that sank due to gravity onto the upper surface of the ethylene-vinyl alcohol copolymer. At this time, the carbon-coated manganese dioxide positive electrode material MnO 2 @MWNT is deposited in the lower layer of the solution due to gravity. After standing for 5 minutes, the first electrode layer, electrolyte layer and second electrode layer are completely separated to obtain a multilayer copolymer.
[0100] (5) The thoroughly stratified ethylene-vinyl alcohol mixed copolymer was immersed in a 1 mol / L lithium chloride electrolyte for 30 min to allow it to be saturated with the lithium chloride electrolyte, thereby preparing a supercapacitor.
[0101] Example 2
[0102] This embodiment provides a method for preparing a flexible asymmetric supercapacitor, which is different from Embodiment 1 in that:
[0103] The carbon-coated manganese dioxide positive electrode material MnO in step (4) 2 The masses of the negative electrode materials FeOOH@MWNT and superparamagnetic carbon-coated iron oxyhydroxide are both 9 mg.
[0104] Comparative Example 1
[0105] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0106] The multi-walled carbon nanotubes in step (2) are 2.5 g, (MnO 2@MWNT carbon nanotube content is 50%);
[0107] The multi-walled carbon nanotubes in step (3) are 0.69 g (the content of FeOOH@MWNT carbon nanotubes is 30%).
[0108] Comparative Example 2
[0109] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0110] The multi-walled carbon nanotubes in step (2) are 2.5 g, (MnO 2 @MWNT carbon nanotube content is 50%);
[0111] The multi-walled carbon nanotubes in step (3) are 1.62 g (the FeOOH@MWNT carbon nanotube content is 50%).
[0112] Comparative Example 3
[0113] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0114] The multi-walled carbon nanotubes in step (2) are 2.5 g, (MnO 2 @MWNT carbon nanotube content is 50%);
[0115] The multi-walled carbon nanotubes in step (3) are 3.78 g (FeOOH@MWNT carbon nanotube content is 70%).
[0116] Comparative Example 4
[0117] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0118] The multi-walled carbon nanotubes in step (2) are 1.1 g, (MnO 2 @MWNT carbon nanotube content is 30%);
[0119] Comparative Example 5
[0120] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0121] The multi-walled carbon nanotubes in step (2) are 2.5 g. (The content of MnO2@MWNT carbon nanotubes is 50%);
[0122] Comparative Example 6
[0123] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0124] The amount of the ethylene-vinyl alcohol copolymer in step (1) is 10 g (the concentration of the ethylene-vinyl alcohol copolymer solution is 0.2 g / mL).
[0125] Comparative Example 7
[0126] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0127] The amount of the ethylene-vinyl alcohol copolymer in step (1) is 15 g (the concentration of the ethylene-vinyl alcohol copolymer solution is 0.3 g / mL).
[0128] Comparative Example 8
[0129] This comparative example provides a method for preparing a flexible asymmetric supercapacitor, which is different from Example 1 in that:
[0130] The carbon-coated manganese dioxide positive electrode material MnO in step (4) 2 The masses of the negative electrode materials FeOOH@MWNT and superparamagnetic carbon-coated iron oxyhydroxide are both 3 mg.
[0131] Comparative Example 9
[0132] This embodiment provides a method for preparing a flexible asymmetric supercapacitor, which is different from the embodiment 1 in that a traditional layer-by-layer stacking method is used:
[0133] In step (1), the ethylene-vinyl alcohol copolymer solution is replaced with an ethylene-vinyl alcohol mixed solution film. The preparation process is as follows: 20 g of ethylene-vinyl alcohol particles and 50 ml of a 1 mol / L lithium chloride solution are mixed and mechanically stirred at 500 r / min for 120 min to obtain an ethylene-vinyl alcohol mixed solution, and then the ethylene-vinyl alcohol mixed solution is poured into a mold and air-dried to obtain an ethylene-vinyl alcohol mixed solution film.
[0134] The first and second electrode layers are freeze-dried and then air-dried to prepare a first electrode layer film and a second electrode layer film. The first electrode layer film, the ethylene vinyl alcohol mixed solution film, and the second electrode layer film are then stacked layer by layer to prepare a conventional non-integrated layer-by-layer supercapacitor.
[0135] The prepared first electrode layer and second electrode layer are respectively coated on both sides of the ethylene-vinyl alcohol mixed solution film.
[0136] Test Case
[0137] The structures and performances of the supercapacitors prepared in the examples and comparative examples were tested.
[0138] 1) Morphology and structure test:
[0139] The cross-section of the supercapacitor prepared in the embodiment and the comparative example was observed using an ultra-depth three-dimensional microscope to observe the morphology of the electrode|electrolyte|electrode interface, wherein, Fig.16 The results of Example 1 and Comparative Example 9 are shown in Fig.16 (Group a is Example 1, Group b is Comparative Example 9, and one vertical row in the figure is one group). It can be seen from the figure that the electrode|electrolyte|electrode of the integrated flexible supercapacitor prepared in Example 1 does not have obvious interface cracking and is fused into an integrated structure. The electrode|electrolyte|electrode of the integrated flexible supercapacitor prepared in Comparative Example 9 has obvious interface cracking and cannot be fused into an integrated structure.
[0140] The cross-section of the supercapacitors prepared in the examples and comparative examples was observed using a cold field emission scanning electron microscope to observe the morphology of the electrode|electrolyte|electrode interface, where groups a, b, and c are the morphologies corresponding to different carbon contents of MnO2@MWNT, and groups d, e, and f are the morphologies corresponding to different carbon contents of FeOOH@MWNT. The results of Example 1 and Comparative Examples 1-5 are shown in Figure 1. Figure 2 (The morphology of both sides of group b and group d is comparative example 1, the morphology of both sides of group b and group e is comparative example 2, and the morphology of both sides of group b and group f is comparative example 3). The results of comparative examples 4 and 5 are as shown in Figure 2 (Group a and Group f are Comparative Example 4, Group b and Group f are Comparative Example 5, Group c and Group f are Example 1), it can be seen that from ac is MnO2@MWNT df is FeOOH@MWNT carbon nanotubes more and more conductive skeletons are getting denser, the surface holes are getting fewer, and the electrochemical performance is getting better; the results of Example 1 and Comparative Example 6 and Example 7 are as follows Figure 3 The results of Example 1, Example 2 and Comparative Example 8 are shown in Figure 8 As shown, it can be seen that from ac is MnO2@MWNT df is FeOOH@MWNT, the carbon nanotubes are becoming more and more, the conductive skeleton is becoming more and more dense, the surface holes are becoming fewer and fewer, and the electrochemical performance is getting better and better.
[0141] 2) Performance test:
[0142] According to GBT 528-2009 standard, the tensile properties of the supercapacitors prepared in Comparative Example 6, Comparative Example 7 and Example 1 were tested, and the elastic modulus, tensile strength, elongation at break and peel strength calculated were as follows: Figure 6 a and 6b, the stress-strain curve is Figure 7 The tensile properties of the supercapacitors prepared in Comparative Example 8, Example 1 and Example 2 were tested, and the elastic modulus, tensile strength, elongation at break and peel strength calculated were as shown in Fig.10 a and 10b, the stress-strain curve is Fig.11 As shown in the figure, it can be seen that the capacitor prepared by the embodiment of the present invention shows that the supercapacitor prepared by the embodiment of the present invention has good mechanical properties.
[0143] The electrochemical performance and impedance test of the supercapacitors prepared in the examples and comparative examples were performed using an electrochemical workstation. Figure 1 It can be seen that the area specific capacitance of the supercapacitors prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 are 82.4, 11.5, 17.01, 44.3, 11.64 and 44.3 mF / cm2, respectively.
[0144] The test results of the supercapacitors prepared in Comparative Example 6, Comparative Example 7 and Example 1 are as follows: Figure 4 As shown. Figure 4 It can be seen that with the increase of EVOH concentration, the area specific capacitance of the supercapacitor gradually increases. The area specific capacitance of the supercapacitors prepared in Comparative Example 6, Comparative Example 7 and Example 1 are 43.7, 68.2 and 82.4 mF / cm2 respectively. The interface transfer resistance of the supercapacitors prepared in Comparative Example 6, Comparative Example 7 and Example 1 are 35, 25.3 and 16.9 respectively. The test results of the supercapacitors prepared in Comparative Example 8, Example 1 and Example 2 are as follows: Fig. 9 As shown. Fig. 9 It can be seen that as the loading of active substances increases to 6 mg / cm2, the area specific capacitance of the supercapacitor has gradually reached the peak value. The area specific capacitances of the supercapacitors prepared in Comparative Example 8, Example 1 and Example 2 are 45.6, 82.4 and 85.9 mF / cm2, respectively. The interface transfer resistances of the supercapacitors prepared in Comparative Example 6, Comparative Example 7 and Example 1 are 48.5, 16.9 and 16.5, respectively. This shows that the supercapacitors prepared in the embodiments of the present invention can exhibit low interface transfer resistance and excellent area specific capacitance by controlling the EVOH concentration and the loading of active substances.
[0145] The flexible supercapacitor prepared in Example 1 was subjected to bending and twisting deformation tests using a flexible electronic tester in conjunction with an electrochemical workstation. The results are as follows: Fig.12 and Fig.13 As shown. Fig.12 The specific capacitance change from 0° to 90° and 180° and the corresponding cyclic voltammetry curve and electrochemical impedance spectrum are shown. Fig.13The capacitance change and the corresponding cyclic voltammetry curves of the integrated flexible supercapacitor prepared in Example 1 after repeated bending between 0° and 180° for 5000 times show that the specific capacitance and electrochemical impedance of the integrated flexible supercapacitor prepared in Example 1 are basically unchanged when bent from 0° to 90° and 180°, and the capacitance retention can reach 99.3% after repeated bending between 0° and 180° for 5000 times. Fig.14 The specific capacitance change from 0° to 20°, 40° and 60° and the corresponding cyclic voltammetry curves and electrochemical impedance spectroscopy are shown. Fig.15 The capacitance change and the corresponding cyclic voltammetry curve of Example 3 after repeated twisting between 0° and 60° for 5000 times show that the specific capacitance and electrochemical impedance of the integrated flexible supercapacitor prepared in Example 3 are basically unchanged from 0° to 20°, 40° and 60°, and the capacitance retention can reach 96% after repeated twisting between 0° and 60° for 5000 times, while the capacitor prepared in Comparative Example 6 shows a large change. The results show that the integrated flexible supercapacitor prepared by the present invention has excellent bending and twisting deformation resistance.
[0146] In order to compare the electrochemical performance of the integrated flexible supercapacitors prepared in the examples and comparative examples, the electrochemical performance of the sandwich structure flexible supercapacitors prepared in Example 1 and Comparative Example 9 was tested using an electrochemical workstation. The results are as follows: Fig.17 As shown. Fig.17 It can be seen that the integrated flexible supercapacitor prepared in Example 1 retains 95% of its capacity after being cycled from 0 to 5000 cycles, while the integrated flexible supercapacitor prepared in Comparative Example 9 retains only 45.2% of its capacity after being cycled from 0 to 5000 cycles.
[0147] The integrated flexible supercapacitor prepared in Example 1 and the conventional flexible supercapacitor prepared in Comparative Example 9 were tested for cycle stability using an electrochemical workstation. The results are as follows: Fig.18 As shown. By comparison, it can be seen that at different scan rates, the area specific capacitance of the integrated flexible supercapacitor prepared in Example 1 is greater than that of the sandwich structure flexible supercapacitor prepared in Comparative Example 9. When the scan rate is 5mV / s, the area specific capacitance of the integrated flexible supercapacitor prepared in Example 1 can reach 82.4mF / cm2, while the area specific capacitance of the sandwich structure flexible supercapacitor prepared in Comparative Example 9 is only 4.17mF / cm2, indicating that the integrated flexible supercapacitor prepared in Example 1 of the present invention has excellent area specific capacitance.
[0148] The electrochemical impedance test of the integrated flexible supercapacitor prepared in Example 1 and the traditional flexible supercapacitor prepared in Comparative Example 9 was performed using an electrochemical workstation. The results are as follows: Fig.19The electrochemical impedance of the integrated flexible supercapacitor prepared in Example 1 is 16.9, while the electrochemical impedance of the sandwich structure flexible supercapacitor prepared in Comparative Example 9 is 49. This indicates that the integrated flexible supercapacitor prepared in Example 1 of the present invention has a lower interface transfer resistance.
[0149] like Fig. 20 and Fig.21 As shown, the integrated flexible supercapacitor prepared in Example 1 can light up electronic clocks in different shapes and under different harsh environments, indicating that the integrated flexible supercapacitor prepared in the present invention can withstand severe external conditions and harsh operating environments and can still be used safely.
[0150] like Fig. 22 As shown, the integrated flexible supercapacitor prepared in Example 1 with three sections connected in series can provide continuous and stable power supply to the electronic bracelet, the pulse oximeter and the intelligent vehicle locator.
[0151] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a flexible asymmetric supercapacitor, characterized in that: The preparation method comprises the following steps: S1, mixing ethylene-vinyl alcohol and an organic solvent and stirring to prepare an ethylene-vinyl alcohol copolymer solution; S2, stirring and mixing the first conductive material, the first energy storage material and the solvent to obtain the first conductive energy storage material, stirring and mixing the second conductive material, the second energy storage material and the solvent to obtain the second conductive energy storage material; S3, mixing the first conductive energy storage composite material, the second conductive energy storage composite material and the ethylene-vinyl alcohol copolymer solution, and layering the mixture using an externally applied magnetic field to obtain a multilayer mixture including a lower electrode layer, an electrolyte layer and an upper electrode layer; S4, placing the multilayer mixture in an electrolyte to obtain a supercapacitor; Wherein, in step S2, the first energy storage material is a non-magnetic material, and the second energy storage material is a magnetic material.
2. The preparation method according to claim 1, characterized in that: In step S1, the organic solvent is selected from at least one of aprotic solvents, aromatic hydrocarbons, halogenated hydrocarbons, acetates, ether solvents or ketone solvents; preferably, the aprotic solvent includes at least one of aprotic, non-polar solvents and aprotic, polar solvents; preferably, the aprotic, non-polar solvent includes at least one of benzene, ether and carbon tetrachloride; preferably, the aprotic, polar solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide and acetone.
3. The preparation method according to claim 1, characterized in that: The content of vinyl alcohol in the ethylene-vinyl alcohol copolymer is 10% to 73%.
4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the first conductive material to the first energy storage material is 1 to 10:1; preferably, in step S2, the mass ratio of the second conductive material to the second energy storage material is 1 to 10:
1.
5. The preparation method according to claim 1, characterized in that: In step S2, the first conductive material and the second conductive material are selected from at least one of carbon nanotubes, graphene, porous carbon, carbon black or carbon fiber.
6. The preparation method according to claim 1, characterized in that: In step S2, the first energy storage material includes at least one of polyaniline, polypyrrole, polythiophene, manganese dioxide, copper oxide, magnesium oxide, vanadium oxide, aluminum oxide, calcium oxide, cuprous oxide, zinc oxide, sodium oxide, potassium oxide and titanium oxide; preferably, in step S2, the second energy storage material includes at least one of iron oxide, nickel oxide, cobalt oxide, ruthenium oxide, hydroxylated iron oxide and ferrosoferric oxide.
7. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the first conductive energy storage composite material, the second conductive energy storage composite material and the ethylene-vinyl alcohol copolymer solution is (1-3): (1-3): 1000; preferably, the concentration of the ethylene-vinyl alcohol copolymer solution is 0.4-0.6 g / mol.
8. The preparation method according to claim 1, characterized in that: In step S3, the intensity of the magnetic field is 20 to 25 emu / g; preferably, in step S3, a magnet is arranged above the mixture, and the distance between the magnet and the mixture is 0.1 to 100 cm.
9. A supercapacitor, characterized in that: The method is as described in any one of claims 1 to 8.
10. A flexible electronic device or a wearable electronic device, characterized in that: It comprises a flexible asymmetric supercapacitor prepared by the preparation method according to any one of claims 1 to 8, or a flexible asymmetric supercapacitor according to claim 9.